2019
DOI: 10.1111/febs.14842
|View full text |Cite
|
Sign up to set email alerts
|

Stroma in normal and cancer wound healing

Abstract: It is currently believed that stroma, the connective framework of biological tissues, plays a central role in normal wound healing and in cancer. In both these contexts, stromal cellular components such as activated fibroblasts interact with complex protein networks that include growth factors, structural protein or proteinases in order to initiate and sustain an extensive remodelling process. However, although this process is usually spatially and temporally self‐limited, it is unregulated in the case of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 90 publications
(120 reference statements)
0
19
0
1
Order By: Relevance
“…CD147 forms complexes with α3β1 and α6β1 integrins by cell-cell contact, which in turn promotes tumor invasion by inducing matrix metalloproteinase (MMP) synthesis via a focal adhesion kinase-(FAK-) PI3K signaling pathway [22]. In addition, CD147 is an inducer of extracellular MMP and suggested to play an important role in cell differentiation due to developmental defects observed in the knockout mice [23][24][25][26]. ese include active differentiation of basal cells in the epithelium, which show a strong and constitutive expression of CD147, whereas a weak expression in the superficial terminally differentiated cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…CD147 forms complexes with α3β1 and α6β1 integrins by cell-cell contact, which in turn promotes tumor invasion by inducing matrix metalloproteinase (MMP) synthesis via a focal adhesion kinase-(FAK-) PI3K signaling pathway [22]. In addition, CD147 is an inducer of extracellular MMP and suggested to play an important role in cell differentiation due to developmental defects observed in the knockout mice [23][24][25][26]. ese include active differentiation of basal cells in the epithelium, which show a strong and constitutive expression of CD147, whereas a weak expression in the superficial terminally differentiated cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis showed a negative correlation between CAFs and a poor prognosis of OSCC patients (Dourado, Guerra, Salo, Lambert, & Coletta, ). CAFs, one of the most dominant components of cancer microenvironment at all stages of progression, are analogues to "factories" that produce a large diversity of molecular factors that reinforce tumor cell proliferation, remodel the structure of the extracellular matrix, alter the metabolic properties of the tumor cells, reprogram the anti‐tumor immune response, facilitate the metastatic process, and define resistance to therapy (Huet et al, ; Kalluri, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is usually composed of connective tissue, the most abundant type of tissue in the body. It connects and supports other tissues and also plays a crucial role in organ development, homeostasis maintenance, and pathologies [4]. The connective tissue consists of cells, mainly fibroblasts, and ECM proteins.…”
Section: Stroma and Tumor Microenvironmentmentioning
confidence: 99%